Concepção(ões) de gestão escolar no processo de implementação das eleições de gestores escolares no município de Tucano/BA - Jesus, Gregório Luís De (2019)
The educational management, since the end of the 1970s, here in Brazil, has been thought as one of the relevant aspects in the fight for the process of democratization of education, defended by forces and many interests, by social movements, public managers and even international companies that provide financial support to countries, as those in Latin American, that propose to follow politics and economical guidelines of these funders organs. Therefore, the accomplishment of this study runs through the complex challenge that the school management has in the process of democratization of education. In this regard, the question set was: which school management conception(s) of school administration oriented the responsible subjects for the implementation process of school managers’ elections in the city of Tucano/BA, and the specifics goals were: a) discuss ideas of democracy, stablishing a relation with the democratic school management conception; b) show management conceptions presents in the school context; c) put the elections implementation process in the city of Tucano/BA into context; d) identify underlying school management conceptions in the subjects responsible for the implementation of the elections in Tucano/BA’s documents and speeches. The methodological path, directed by the assumptions of the qualitative approach, had as information collection tools the semi-structured interview, the closed survey, focus group and documental analysis. The 09 (nine) subjects that participated in the research were selected based in the direct involvement in the implementation of Tucano/BA’s school managers criterion. To the data collected interpretation, the Franco (2005) and Bardin (2016) content analysis was used. The theoretical discussions that served as baseline to the study are aligned to the critical theory. This study sought to contribute with the school management historiographical process inside the city of Tucano, as well as the school management mapping in the Sisal’s Identity Territory and in Bahia, for being integral part of a research project that belongs to Studies and Researches about Teachers Training Core (NUFOP/UEFS). The results points to a democratic school management legitimation as official speech present in the subjects’ lines and in the produced documents, however, they also revealed the tensions, disagreements and disputes that surrounds different education process and society. As a collaboration tool in the school management democratization process, the principal’s elections, although recognized as one of the essentials elements, in this study shows itself crossed by clientelistics, managerialists, patrimonialists, conservatives and burocratics, which difficult the concretization of a society project committed to socials inequalities decrease.